Gestão do trabalho em saúde pública : discurso, paráfrase e polissemia - Arsego, Lívia Ramalho (2017)
This study had the objective to comprehend the process by which the terminology Health Work Management emerged in the area of Brazilian public health, especially in the year of 2003, replacing the term Human Resources, which was traditionally used in reference to the work force in organizations. Based on the Social Work’s Ethical Political Project (PEP), formalized through the Code of Ethics (CE), questions were raised on the evidences and possibilities of meanings inherent in literacy. Relying on historical materialism and contributions from Discourse Analysis based in Pêcheux’s work, which relate to the conception of material and historical construction of discourse, and its heterogeneities, to its objective interventional capacities and to the understanding of the work of constant reformulation of ideology of the ruling class, which shows the absorption of movements of resistances and oppositions. To this process of reinforcement to the reproduction of the order of capital, to which it is restricted in circularity and limits the analytical possibilities of this discursive approach, it is possible to approximate its preponderance as a dynamic of daily life, and refers to the possibilities of ethical reflection aiming suspensions and construction of overruns, in a commitment to the assumptions and values contained in the professional CE. To understand the effects of meaning produced from the word Work Management in Health, and terminological substitution act, we returned to the design of the conditions of production to which these articulations and interventions of distinct discursive memories are related. From the meanings denoted by the linguistic materialities at those intersection of work, health and management, it was shown that work and health had the funcionality to produce opposing meanings, generating displacements by associating themselves with the meanings of the management word, to which the maintenance and prevailing functions of capitalism. Thus, the presence of the term management in the new terminology referring to work relations in health involves convergent meanings to the hegemonic processes, at the same time that there is a tension exerted in the direct composition to the terms work and health, including the contradictory processes between paraphrase and polysemy. In a world context where management practices are conformed with neoliberalism, of worsening social conditions and of protection to work, in the discursive process dominant in the Official Discourse (DO) of the period preponderates this operation, to which it is emphasized the importance of the displacements associated to the meanings of work and health, which establish relationship with the historical agenda of health workers, to obtain social support for the actions that resulted in greater capillarization of capital in public establishments. At the same time, it affirms the importance of the struggles that allowed re9 significations and rearticulation of the networks of meaning. This movement is not to justify the adaptive capacities of the dominant ideology, but to consider, according to the Social Work’s CE, the possibilities of acting within the limits of the bourgeois order, to recognize levels of political and social emancipation that guarantee conditions and security of life to the subaltern classes, reiterating them as a relevant part of a compromised project for human emancipation, for which the potentialities of the ethical-political praxis on Marxism bases are recognized.